2002
DOI: 10.1177/107906320201400207
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Collaborative Outcome Data Project on the Effectiveness of Psychological Treatment for Sex Offenders

Abstract: This meta-analytic review examined the effectiveness of psychological treatment for sex offenders by summarizing data from 43 studies (combined n = 9,454). Averaged across all studies, the sexual offence recidivism rate was lower for the treatment groups (12.3%) than the comparison groups (16.8%, 38 studies, unweighted average). A similar pattern was found for general recidivism, although the overall rates were predictably higher (treatment 27.9%, comparison 39.2%, 30 studies). Current treatments (cognitive-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
478
9
20

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 742 publications
(537 citation statements)
references
References 46 publications
24
478
9
20
Order By: Relevance
“…Examining the results of 30 studies together, Hanson et al (2002) found, for an average follow-up of 46 months, general recidivism rates (i.e., any type of crime) of 28% for treated and 39% for untreated sexual aggressors following their release. These numbers were higher than those found for sexual recidivism, that is, 12 and 17% for treated and untreated participants respectively.…”
Section: Sexual Offenders and Recidivism Studiesmentioning
confidence: 99%
“…Examining the results of 30 studies together, Hanson et al (2002) found, for an average follow-up of 46 months, general recidivism rates (i.e., any type of crime) of 28% for treated and 39% for untreated sexual aggressors following their release. These numbers were higher than those found for sexual recidivism, that is, 12 and 17% for treated and untreated participants respectively.…”
Section: Sexual Offenders and Recidivism Studiesmentioning
confidence: 99%
“…Recidivism rates of all categories are significantly reduced for sex offenders who have undergone Cognitive Behavioral Therapy, (Craig, Browne & Stringer 2003;Hanson, Gordon, Harris, Mareques, Murphy, Quinsey, & Seto 2002;Lösel & Schmucker, 2005;Luong & Wormith, 2006;& MacKenzie, 2006), except for pedophiles whom are excluded from this research. Sex offenders who participate in community-based treatment programs are likely to reduce their likelihood of recidivating even more (Aytes, Olsen, Zakrajsek, Murray & Ireson, 2001).…”
Section: Rehabilitationmentioning
confidence: 99%
“…Though sex offenders have served their sentence, a feat that pays off many other types of offenders" debt to society, sex offenders are still forced in to a life-time worth of punishment beyond incarceration. Though recidivism rates for sex offenders have proven to be some of the lowest (Hanson & Morton-Bourgan, 2005;Harris & Hanson, 2004;& Tewksbury, Jennings & Zgoba, 2012), and many sex offenders go through effective treatment programs pre-and-or-post-release (Aytes, Olsen, Zakrajsek, Murray & Ireson, 2001;Craig, Browne & Stringer 2003;Hanson, Gordon, Harris, Mareques, Murphy, Quinsey, & Seto 2002;Lösel & Schmucker, 2005;Luong & Wormith, 2006;& MacKenzie, 2006), our society still feels that we need to add more layers of protection. While community safety is of great importance, does it constitute the negative toll it takes on the lives of sex offenders?…”
Section: Punishment Beyond Incarcerationmentioning
confidence: 99%
“…Aux États-Unis, en outre, les coûts associés à l'utilisation accrue de la prison ainsi que des peines plus longues et fi xes ont mené à une baisse des possibilités de traitement et de réadaptation (Travis et Petersilia, 2001). Au Canada, tandis que les efforts de réhabilitation restent une partie intégrante de l'objectif de justice pénale, le traitement a été mis en arrière-plan à l'égard des objectifs de gestion du risque, et ce, en dépit de preuves empiriques qui suggèrent un effet positif des programmes de traitement des délinquants sexuels (par exemple Hanson et al, 2002 ;Lösel et Schmucker, 2005 ;Mackenzie, 2006). Cette gestion du risque a été élaborée à partir de l'hypothèse qu'il y a une certaine stabilité de l'activité criminelle et du risque de récidive des délinquants sexuels.…”
Section: Introductionunclassified